PERANCANGAN SISTEM INFORMASI DASHBOARD DATA KEPENDUDUKAN PADA DESA SUKAMANAH KECAMATAN BAROS KOTA BANTEN - Muhammad Farhan (2021)
The problem with data management in Indonesia at this time era still the quite risky issues, considering that this era of globalization has entered the modern era where the information is needed very quickly dan accurately, one of this fast and accurate information is indispensable at the village office to help the performance of employees in changing, finding and searching population data and making it easier for employees to write letters. In this case, the village office that is located in Sukamanah Village still does not have an information system that makes it easier for employees to manage population administration books because the management process at the village office is still manual and has low understanding of employees in using technology and it takes several days to recapitulate population data once in a year. Therefore, in order to improve the services at the village office, it needed a system that intend to manage the administration book of population data, so that the data can be obtained quickly and accurately. The information system is web-based which can be accessed on any platform. The method that will use in making the information system is waterfall method. The expected result of the research is the creation of an information system that can assist village office employees in providing direct services to villagers, especially in administration book of population data.